Wybrane elementy z zakresu budżetowania portfela projektów - Klinowski, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Management by projects is more and more often applied by companies nowadays. The foregoing paper presents some issues in the field of the projects portfolio budgeting. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 131-136